Understanding the effects of prompting immediately after problem behavior occurs during functional communication training. Issue 1 (19th November 2021) - Landa, Robin K.; Hanley, Gregory P.; Gover, Holly C.; Rajaraman, Adithyan; Ruppel, Kelsey W.
Abstract : When reported, the methods for prompting functional communication responses (FCRs) following problem behavior during functional communication training (FCT) vary. Some researchers have prompted the FCR immediately following problem behavior but doing so may inadvertently strengthen problem behavior as the first link in an undesirable response chain. This study investigated the effects of prompting FCRs following problem behavior during FCT with 4 children who exhibited severe problem behavior. Problem behavior remained low and FCR rates were near optimal when prompts were delivered immediately following problem behavior for 2 participants. Delaying prompts following problem behavior was instrumental for FCR acquisition for 1 participant but led to escalation of problem behavior for a 2nd participant. The conditions under which immediate prompts following problem behavior may improve or worsen FCT are discussed.